2015
DOI: 10.1097/hmr.0000000000000006
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, safety climate, and continuous quality improvement

Abstract: The notion that patient safety climate and CQI initiatives are not interchangeable or universally beneficial is an important contribution to the literature. The results confirm the importance of using CQI to effectively enhance process quality in hospitals, and patient safety climate to improve patient safety outcomes. The overall pattern of findings suggests that simultaneous implementation of CQI initiatives and patient safety climate produces greater combined benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 31 publications
4
107
0
6
Order By: Relevance
“…By enlarging the organisational distance, Xirasagar, Samuels, and Stoskopf (2005) revealed that medical directors scoring higher for transformational behaviour were more effective in terms of clinical goal achievement and subordinates' extra efforts. The latest research evidence suggests that higher safety perceptions and quality improvement efforts in hospitals may be traced back to chief executive officers' (CEO) transformational behaviour (McFadden, Stock, and Gowen 2015). As such, hospital executives' transformational behaviour appears to be an effective way of creating a work environment that prioritises safety and quality of care.…”
Section: Theory and Hypothesismentioning
confidence: 98%
“…By enlarging the organisational distance, Xirasagar, Samuels, and Stoskopf (2005) revealed that medical directors scoring higher for transformational behaviour were more effective in terms of clinical goal achievement and subordinates' extra efforts. The latest research evidence suggests that higher safety perceptions and quality improvement efforts in hospitals may be traced back to chief executive officers' (CEO) transformational behaviour (McFadden, Stock, and Gowen 2015). As such, hospital executives' transformational behaviour appears to be an effective way of creating a work environment that prioritises safety and quality of care.…”
Section: Theory and Hypothesismentioning
confidence: 98%
“…Only then-in a climate of change [15]-medication safety projects may prosper beyond time-limited pilot projects. Indeed, a leadership facilitating and supporting a safety climate in an institution might foster quality improvement initiatives which again may translate into patient safety [16]. As safety climate was also identified as an independent predictor for patient safety, it is even more important to work on the overall safety climate of an institution in addition to introduction of specific quality improvement strategies [16].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a leadership facilitating and supporting a safety climate in an institution might foster quality improvement initiatives which again may translate into patient safety [16]. As safety climate was also identified as an independent predictor for patient safety, it is even more important to work on the overall safety climate of an institution in addition to introduction of specific quality improvement strategies [16]. Internal [17] and external benchmarking [18] might help to support a longitudinal improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Hirtz et al (2007), when correlating the transformational, transactional and laissez-faire leadership styles with organizational performance according to the criteria of the Baldrige Quality Award, found out the level of perception of quality management implementation in the administrative and service departments was positively related to transformational and transactional leadership, and negatively related to the laissez-faire style. McFadden et al (2015) founded evidences that a security climate, that is connected to a transformational leadership style, relates to the implementation of quality continuos improvement process, and quality improvement process in hospitals.…”
Section: Quality Management and Transformational-transactional Leadermentioning
confidence: 99%